The Essence and Existence of Kalam Science - Nahdatul Khairunisa; Martin Kustati; Nana Sepriyanti (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
The science of kalam is the science that discusses divine problems and various problems related to them based on convincing arguments. The science of Kalam is also called the science of monotheism, the science of aqidah, the science of ushuludin, and the science of Fiqh al-akbar because it is the issue of belief which is the subject of religious teachings that is the subject of discussion. The essence of the science of kalam is to make us more confident in what we believe in Allah based on the arguments of naqli and the arguments of aqli. The main problem of Kalam Science lies in three issues, namely the Essence of God Himself with all His attributes, Qismul Nububiyah, the caring relationship between Kholik and creatures, Issues relating to life after death which will later be called Qismul Al-Sam'iyat.